Running demands and activity profile of the new four-quarter match format in men's field hockey - Ihsan, M.; Yeo, V.; Tan, F.; Joseph, R.; Lee, M.; Aziz, A. R. (The Journal of Strength and Conditioning Research, 2021)
This study determined the running demands of men's field hockey with regards to the revised four-quarter match format. Twenty-eight male field hockey players were equipped with global positioning system units while competing in 14 competitive international games over a 1-year period. All matches allowed for unlimited substitutions, and consisted of four 15-minute quarters (i.e., Q1—Q4). A progressive decline in total distance (TD) was observed in Q2 (2,072 ± 141 m) to Q4 (2,055 ± 212 m) compared with Q1 (2,171 ± 195 m, p < 0.05). However, the decline in TD was due to decreases in low-intensity activity (<15 km/h, p < 0.05), as high-intensity running (HIR; >15 km/h) distances were similar throughout Q1—Q4 (p = 0.263). Positional data demonstrated a similar profile, where significant decreases in TD, but not in HIR, was observed across all playing positions at some point over the 4 quarters (p < 0.05). DEF accumulated the lowest amount of TD (7,631 ± 753 m), HIR (2,257 ± 498 m), and high-intensity decelerations (60 ± 9, >-2 m/s2) compared with MID and FWD (p < 0.05). By contrast, FWD performed the highest amount of HIR (3,090 ± 565 m) and high-intensity accelerations (110 ± 9, >2 m/s) compared with MID and DEF (p < 0.05). In conclusion, our results showed that although there was a progressive decline in TD over the 4 quarters of match play, high-intensity running performance (i.e., HIR and high-intensity acceleration) was maintained throughout the match regardless of playing position.